Modeling the Future of Prevention in Primary Mental Health Care: A Narrative Literature Review - Sara J. Doyle, MD, MPH; Jordyn H. Feingold, MD, MSCR, MAPP; Thomas J. Van Gilder, MD, MPH (Elsevier, 2023)
Introduction: Adults in the U.S. have had poor and worsening mental health for years. Poor mental health exacts a high human and economic cost. Methods: Using PubMed, we conducted a focused narrative literature review on mental well-being and its role in mental and physical health care. Results: Mental well-being is essential for mental and physical health. High mental well-being is associated with a lower incidence of psychiatric disorder diagnosis and better function for those who do carry a formal diagnosis. High mental well-being also improves health outcomes for several physical diseases. Cultivating mental well-being is both a primary and secondary prevention strategy for mental and physical illness. There is a growing number of low-cost and accessible interventions to promote mental well-being, rooted in the research of positive psychology. These interventions improve mental well-being in multiple populations from different cultural backgrounds. There have been some efforts to incorporate these interventions to improve mental well-being in the clinical setting. Conclusions: Our mental healthcare system would substantially improve its ability to protect against mental illness and promote positive function if mental well-being was routinely measured in the clinical setting, and interventions to improve mental well-being were routinely incorporated into standard primary and specialty care.